Productivity and Feasibility of Tuna Longliner on Cilacap District Central Java - Suradi Wijaya Saputra; Anhar Solihin; Dian Wijayanto; Faik Kurohman (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
ABSTRACT Tuna Longliner or Tuna Longliner is fishing gear for a large pelagic fish, including Tuna. One unit of Tuna Longlinerr usually operate are 1000-2000 off the hook for once. Tuna Longliner generally operated on the high seas or ocean waters. Fuel is the largest production factor of Tuna Longliner. Fuel prices tend to rise is expected to affect the productivity and business feasibility. This study aims to assess the productivity and business feasibility Tuna Longliner at Cilacap district. Research carried out in PPS Cilacap in August until September 2008, using survey methods. Primary data collected are: the price of fish, size of vessel (GT), composition of the catch, and volume production. While secondary data is captured fish production of Tuna Longliner and fishing trip. Analysis of production data and produksivity using descriptive statistics, presented in the curves. Business feasibility analysis performed by calculating the NPV, IRR, and payback periods.  The results showed that the productivity of Tuna Longliner of Cilacap district is relatively low (0.045 tons / GT / year). The low of productivity due to the occurrence of a fully-exploited. This apparently resulted in a fishing business using Tuna Longliner of Cilacap district is not feasible, based on indicators of NPV, IRR, and payback periods. This condition requires that the management of serious action from government. Keyword: Tuna Longline, produktivity, feasibility.